2005
DOI: 10.1258/0969141054855328
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of visual inspection with acetic acid (VIA), Lugol's iodine (VILI), cervical cytology and HPV testing as cervical screening tools in Latin America: This report refers to partial results from the LAMS (Latin AMerican Screening) study

Abstract: The LAMS study failed to reproduce the performance figures obtained with VIA and VILI (as stand-alone tests) in some other settings, where the prevalence of cervical disease was higher. However, a combined use of VIA or VILI with the Pap test or HCII allowed specific detection of cervical abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
92
3
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(115 citation statements)
references
References 22 publications
15
92
3
5
Order By: Relevance
“…The results, however, are very similar to those of the LAMS study carried out in Brazil and Argentina. 14 When follow-up and referral for treatment are difficult, there is a substantial advantage of having an immediate result from screening. This, however, has to be balanced against the overtreatment that would result from offering cryotherapy (or LEEP without prior biopsy) to all women who screen positive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results, however, are very similar to those of the LAMS study carried out in Brazil and Argentina. 14 When follow-up and referral for treatment are difficult, there is a substantial advantage of having an immediate result from screening. This, however, has to be balanced against the overtreatment that would result from offering cryotherapy (or LEEP without prior biopsy) to all women who screen positive.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the Hybrid Capture II test can be automated; the results are not subject to human judgement; they have been successfully implemented in several Latin American laboratories and have shown excellent inter-laboratory agreement. 14,[27][28][29][30][31][32][33][34][35][36] There was only one insufficient sample for testing, a remarkable achievement compared to inadequate rates for cytology (5% for LBC and 11% for CC).…”
Section: Hpv Testingmentioning
confidence: 99%
“…The screening process, along with the delays between screening, test results and ultimate treatment are major obstacles to the success of cytology-based programs in low-resource settings. Although cytology screening has been introduced in LMIC over the past 30 years, it has not resulted in the expected decreases in cervical cancer incidence and mortality similar to those observed in the HIC, primarily because of the above mentioned hurdles associated with low coverage of the target population (Dzuba et al, 2005 the CIN2 and CIN 3 (53% in HIC, and 26-65% in LMIC) (Almonte et al, 2007;Cuzick et al, 2006;Sankaranarayanan et al, 2004b;Sarian et al, 2005), repeated screening at regular intervals is necessary for the programmes to be effective. This low sensitivity in developed countries is overcome by organized periodic screening, which is not feasible with the opportunistic screening carried in low-resource setting.…”
Section: Cytologymentioning
confidence: 99%
“…During the last decade, alternatives to cytological screening have been evaluated in low-resource settings (Belinson et al, 2001;Ferreccio et al, 2003;De Vuyst et al, 2005;IARC, 2005;Sarian et al, 2005;Sangwa-Lugoma et al, 2006;Almonte et al, 2007;Pretorius et al, 2007;Sankaranarayanan et al, 2007). Visual inspection with acetic acid (VIA) is a low-cost option that allows the possibility of screening and treatment in one visit (Denny et al, 2005), and has been shown to significantly reduce cervical cancer mortality in a large randomised controlled trial (Sankaranarayanan et al, 2007).…”
mentioning
confidence: 99%